2013
DOI: 10.3928/01477447-20130327-21
|View full text |Cite
|
Sign up to set email alerts
|

Bifid Median Nerve Causing Carpal Tunnel Syndrome: MRI and Surgical Correlation

Abstract: Carpal tunnel syndrome can be secondary in some patients, and vascular anomalies (usually a persistent median artery), median nerve variations, or both are among the etiologic factors. High division of the median nerve proximal to the carpal tunnel (known as a bifid median nerve) is a median nerve anomaly that has an incidence rate of 2.8%. This rare entity is often associated with various abnormalities that are clinically relevant, such as vascular malformations (persistent median artery), aberrant muscles, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 27 publications
0
25
0
4
Order By: Relevance
“…Previous studies and several case reports have suggested that bifid median nerve occurs relatively frequently in patients with CTS 4-7. However, this conclusion is controversial.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies and several case reports have suggested that bifid median nerve occurs relatively frequently in patients with CTS 4-7. However, this conclusion is controversial.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, it is important for surgeons to be aware of these structural variations when planning carpal tunnel release or other surgeries associated with carpal tunnel syndrome (CTS). Several studies have implicated bifid median nerve and persistent median artery as potential risks for CTS 4-7. However, this hypothesis has been disputed.…”
Section: Introductionmentioning
confidence: 99%
“…Occasionally, we met a healthy case with a bifid median nerve variation caused by the persistent median artery, which was regarded as a potential etiology for CTS [15] (Fig. 11).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have showed that bifid median nerve and PMA association is a potential risk for CTS 5. A bifid median nerve and PMA are anatomic variants that have been reported widely in the surgical literature.…”
Section: Discussionmentioning
confidence: 99%